AN ALTERNATIVE APPROACH ON BIOREMEDIATION OF HEAVY METALS IN TANNERY EFFLUENTS WASTE USING STREPTOMYCES SP. - D, Thirumurugan; Adamu Karfi, Ibrahim; R, Vijayakumar; Tg, Nithya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The present study is conducted to investigate the abilities of microorganisms to degrade heavy metals in industrial tannery effluent sample. Methods: Tannery effluent sample was collected from effluent treatment plant and analyzed for physicochemical parameters. The potential microbes were isolated and identified by morphological and biochemical characterization. The sample was analyzed before and after to assess the heavy metal reducing the ability of the microorganism and the respective percentage of reduction were studied using X-ray fluorescence spectrometry. Results: The samples were initially found to be highly contaminated with chromium, nickel, and cadmium. Out of three potential isolates, the isolate Streptomyces sp. was found to exhibit a better reduction against chromium (25.7%), cadmium (14.6%), and nickel (23.1%) in 50 ppm at longer incubation period. Comparatively, the reduction abilities of all the three isolates against all the three heavy metals increased with the increase in the incubation period but decreased with the increase in initial metal ion concentration except in the case of Streptomyces sp. against nickel where the reducing ability increased with the increase in metal concentration. Conclusion: Apparently, the present study revealed that Streptomyces sp. had a better remediation potential than the indigenous Pseudomonas sp. and Aspergillus sp. Ultimately, the finding of this research has shown that the Streptomyces sp. can be used as a potent bioremediation agent for treating tannery and industrial effluent in an eco-friendly process.